Turkish school teachers’ knowledge and attitudes toward HIV/AIDS - Nur, Naim (Croatian Medical Schools, 2012)
AIM: To assess Turkish school teachers’ knowledge, attitudes, and misconceptions of HIV/AIDS. METHODS: This cross-sectional descriptive study was conducted in Sivas, Middle Anatolian province of Turkey, from January to May 2009. We selected and interviewed 898 teachers using a simple systematic sampling method. RESULTS: All respondents heard about AIDS. Most knew that it could be transmitted by infected blood (98.0%) and sexual contact (93.4%) and some (33.2%) thought that it could be transmitted by mosquitoes. Although the majority of them strongly agreed or agreed with the statement that “people with AIDS should be helped, supported and treated” (98.0%), about 40% and 70% of them, respectively, agreed or strongly agreed with the statement that infected people should be quarantined. Young teachers with a higher level of knowledge about HIV/AIDS had more positive attitudes. CONCLUSION: This study provided basic information on school teachers’ AIDS knowledge and attitudes and showed that various misconceptions of HIV transmission were a matter of concern. A considerable number of respondents with undesirable attitudes toward HIV/AIDS indicates the need for education of teachers on the subject.